Body performance standards of healthy Malaysians: adult range of fitness level - Hussin, I.H.; Usman, Juliana; Wan Abas, Wan Abu Bakar; Abu Osman, Noor Azuan (2007)
The use of exercise as a condition from which to investigate bodily function can be dated back to the ancient times of the first Olympic whereby features that was performed by the body were observed and specific training program were devised to foster improvements. For years Malaysian has been depending on the American and the European fitness standards as a guideline for our athletes and fitness health grading purposes. However, we ought to have our own since there are so many differences between us; Asians and them, be it social lifestyles or nutritional intake. This paper presents a preliminary standard of physical fitness by healthy Malaysians from the adult age group as a benchmark.